Socioeconomic and clinical factors influencing treatment selection in microtia and aural atresia. (February 2021) - Ghadersohi, Saied; Haville, Salina; Hedman, Megan; Adkisson, Kirsten; Cooper, Emily; Kaizer, Alexander; Gitomer, Sarah A.; Kelley, Peggy E.
Abstract: Objectives: Patients with microtia and aural atresia have multiple options for treatment of conductive hearing loss (CHL) and auricle reconstruction; however, little is known about the factors influencing treatment selection. This study aims to review the socioeconomic and clinical data of microtia/atresia patients to evaluate congruency with national data and whether these factors affect treatment decisions. Methods: Retrospective review of patients evaluated in the microtia and atresia multidisciplinary clinic (MDC) at a tertiary academic children's hospital between 2008 and 2018. Outcomes included demographic, socioeconomic and clinical factors associated with hearing surgery and framework surgery. Results: 373 patients were seen in the Microtia MDC: 193 (51.7%) were male, 187 (50.1%) identified as Hispanic and 23 (6.2%) identified as Asian. 267 (75.6%) patients received a nonsurgical bone conduction hearing device (BCHD); fitting at a younger age was associated with better nonsurgical BCHD compliance. Multivariate analysis was performed on the patients that were eligible for surgery based on age and appropriate follow-up. 70 (18.8%) patients had placement of an osseointegrated BCHD; inconsistent compliance with nonsurgical BCHD decreased the odds of proceeding with osseointegrated BCHD placement. 60 (16.1%) patients underwent framework surgery for external reconstruction. Placement of osseointegrated BCHD was the only factor that was associated with proceeding with framework surgery. Other assessed demographic and socioeconomic factors were statistically not associated with selection of surgical intervention. Conclusion: Fitting a nonsurgical BCHD at a younger age is associated with higher likelihood of nonsurgical BCHD compliance, that is in turn associated with patients and families proceeding with osseointegrated BCHD and framework surgery.